Acclimation and endogenous abscisic acid in the moss Physcomitrella patens during acquisition of desiccation tolerance. Issue 3 (13th February 2019) - Rathnayake, Kumudu N.; Nelson, Sven; Seeve, Candace; Oliver, Melvin J.; Koster, Karen L.
Abstract : The moss Physcomitrella patens has been used as a model organism to study the induction of desiccation tolerance (DT), but links between dehydration rate, the accumulation of endogenous abscisic acid (ABA) and DT remain unclear. In this study, we show that prolonged acclimation of P. patens at 89% relative humidity (RH) [−16 MPa] can induce tolerance of desiccation at 33% RH (−153 MPa) in both protonema and gametophore stages. During acclimation, significant endogenous ABA accumulation occurred after 1 day in gametophores and after 2 days in protonemata. Physcomitrella patens expressing the ABA‐inducible EARLY METHIONINE promoter fused to a cyan fluorescent protein (CFP) reporter gene revealed a mostly uniform distribution of the CFP increasing throughout the tissues during acclimation. DT was measured by day 6 of acclimation in gametophores, but not until 9 days of acclimation for protonemata. These results suggest that endogenous ABA accumulating when moss cells experience moderate water loss requires sufficient time to induce the changes that permit cells to survive more severe desiccation. These results provide insight for ongoing studies of how acclimation induces metabolic changes to enable DT in P. patens .